Konseling Gizi, Kualitas Diit Berbasis Pangan Lokal Dengan Kadar Glukosa Darah Penderita Diabetes Mellitus Tipe Ii Di Wilayah Kerja Puskesmas Bahu - Rivolta G,M, Walalangi; Muksin Pasambuna; Rudolf B. Purba; Agung Suryohadi (POLTEKKES KEMENKES MANADO, 2018)
Diabetes Mellitus is a group of chronic disease which is characterized by increased levels of glucose in the blood due to disorders of the body's metabolism system, in which the pancreas organ incapable of producing the hormone insulin according to needs of the body. Nutritional counselling with quality local food based diit can help control blood glucose levels. This research aims to identify the difference in blood glucose levels and the value of quality diit type II diabetes mellitus patients before and after given nutritional counseling with quality local food based diit. This type of research is Pre Experimental research using one group pretest-posttest design. The number of samples is determined by purposive sampling counted 31 people. Data analysis using Wilcoxon and T-test analysis. The Wilcoxon analysis with significance level of 95% can be seen to produce significant difference in pre-post glycemic index component with p=0,000 (p<0,05) and diversity of pre-post food with p=0,002 (p<0,05). In the result of T-test for pre-post blood glucose variable, there was no significant difference p=0,105 (p>0,05). However, there was a range of decreased glucose levels before and after in 22 respondents with an average decrease of 11.42 mg/dL. Conclusion there was no difference of blood glucose level before and after nutrition counseling with quality of diet based on local food.